Wyrok ETPC jako precedens wiążący quasi de iure a efektywność porządku Europejskiej Konwencji Praw Człowieka (perspektywa teoretycznoprawna): [Judgment of the ECHR as a precedent binding quasi de Iure and the effectiveness of the European Convention on Human Rights (theoretical perpective)] (Studia Prawnicze / The Legal Studies, 2017)
Niniejszy artykuł poświęcony jest teoretycznej refleksji nad precedensowym charakterem wyroków Europejskiego Trybunału Praw Człowieka (dalej ETPC lub Trybunał). Rozważania będą prowadzone z perspektywy kontynentalnej kultury prawnej i z pełną świadomością braku możliwości kwalifikowania wyroku ETPC jako precedensu w rozumieniu, jakie nadaje się tej instytucji w porządkach prawnych common law. Odwoływanie się do anglosaskiej konstrukcji precedensu będzie dokonywane tylko na potrzeby dokonywania porównań. Celem autora jest poddanie analizie argumentów przemawiających zarówno za, jak i przeciw możliwości uznania wyroków Trybunału za precedensowe, a nie dogmatyczna analiza wyroków Trybunału i zakres, w jakim wiążą one organy (przede wszystkim stosujące prawo) państw członkowskich Rady Europy In the system of the European Convention on Human Rights (ECHR or the Convention), the basic formula for creating standards for the protection of human rights is to define their understanding of and possible modifications or changes as a result of a law-making interpretation of the provisions of the Convention. The substantive rules of the Convention since its inception, not only have not changed (they were amended or derogated), but in addition are very general. This causes, that the way their understanding sets the European Court of Human Rights (ECHR or tribunal) forming in a legislative standards for the protection of human rights. That raises the interesting question of theoretical, since in public international law on the one hand the judgment of an international court is recognized as an auxiliary source of international law (art. 38 sec. 1 point d Statute of the International Court of Justice), while not applicable rule of stare decisis, meaning legally bound judgment precedent of other courts in similar cases. If, however, a violation of well-established case law of the ECHR by the national authorities is the reason for the judgment of the committee of three judges without a hearing (art. 28 paragraph. 1 point b ECHR). Judgments of the Court (the monopoly of interpretation of the ECHR) must be respected and enforced in order of national law (Art. 46 paragraph. 1 and 2 of the ECHR). This raises the natural question of the scope of their precedensowości for the tribunal and law enforcement organs in the national legal system. It is with this problem both theoretical and practical. The obvious fact is that the decision of the ECHR does not create a precedent in the sense of how suitable term in common law. However, its decisions affect application of the law on domestic, not only in reality, but partly also legal, so that it can be concluded that the judgment has the power of the normative and, to some extent binding. But what is the scope of the precedent character of this sentence? The answer to this question is the subject of considerations to be taken in the paper.